Personal pronouns Ité as politeness marker in Manggarai language and culture, Indonesia - Ignas Loy Semana; Sebastianus Menggo (Universitas Islam Sultan Agung, 2022)
Culture is about human existence and the way of life, while language is about the communication system between people in a particular society or community. Language use usually reflects the habits of society, the way of thinking, the work of the brain, the history of society, and the internal relationship in society. The use of personal pronoun inclusive we ité in Manggarai language helps speakers find out the relationship between linguistic aspects and cultural values. Based on these arguments, this study aims to analyze the relationship between the two aspects that are being addressed. The data were collected through observations and interviews of the ten traditional spokespersons, then analyzed qualitatively. The finding indicates that the use of ité in all of its forms reflects the etiquette of people in Manggarai, Indonesia. Referring to the data stated, this study, therefore, concludes that the first personal pronoun plural inclusive we ité, in Manggarai language and culture demonstrates the speaker's politeness and humility in front of the hearer or listener; the speaker truly respects the interlocutor; to convey high regard for the interlocutor in a high position; to prove tribute, respect, and admiration; to show intimacy, closeness, and fraternity in the social relationship; and to show a great homage to Supreme Being.